The 157 Month Swift/BAT All-sky Hard X-Ray Survey - Amy Y. Lien; Hans A. Krimm; Craig B. Markwardt; Kyuseok Oh; Lea Marcotulli; Richard Mushotzky; Nicholas R. Collins; Scott D. Barthelmy; Wayne H. Baumgartner; S. Bradley Cenko; Michael Koss; Sibasish Laha; et al. (The Astrophysical Journal)
The Burst Alert Telescope (BAT) on board the Neil Gehrels Swift Observatory has been serving as a survey instrument for the hard X-ray sky, and has detected thousands of X-ray sources (e.g., active galactic nuclei, X-ray binaries, etc). BAT monitors these X-ray sources and follows their light curves on timescales from minutes to years. In addition, BAT has discovered hundreds of new X-ray sources in survey images stacked throughout the mission lifetime. We present an updated BAT survey catalog since the last published BAT 105 month survey catalog with additional 4.5 yr of data until 2017 December. Data since 2007 are reprocessed to include updated instrumental calibrations. Analysis in this study shows that additional systematic noise can be seen in the 157 month mosaic images, resulting in decreases in the expected improvement in sensitivity and the number of new detections. The BAT 157 month survey reaches a sensitivity of 8.83 × 10 ^−12 erg s ^−1 cm ^−2 for 90% of the sky and 6.44 × 10 ^−12 erg s ^−1 cm ^−2 for 10% of the sky. This catalog includes spectra, and monthly and snapshot light curves in eight energy bands (14–20, 20–24, 24–35, 35–50, 50–75, 75–100, 100–150, and 150–195 keV) for 1888 sources, including 256 new detections above a detection threshold of 4.8 σ . The light curves, spectra, and tables that summarize the information of the detected-sources are available in the online journal and on the catalog web page: https://swift.gsfc.nasa.gov/results/bs157mon/ .